2010
DOI: 10.1002/yea.1830
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phosphatase 2A‐like Sit4‐mediated signalling and ubiquitin‐dependent protein sorting as modulators of caffeine sensitivity in S. cerevisiae

Abstract: Caffeine exerts pleiotropic effects on eukaryotic cells via its ability to act as a lowaffinity adenosine analogue. Here we report that the genes HSE1, RTS3, SDS23 and SDS24 confer caffeine resistance when overexpressed in S. cerevisiae. The Hse1 protein functions in ubiquitin-dependent vacuolar protein sorting, whereas the other proteins are poorly characterized. Bioinformatic analysis of genetic and physical interaction data linked Rts3 and Sds23/24 to the phosphatase 2A-like Sit4 pathway. Combinatorial dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 77 publications
(129 reference statements)
2
6
0
Order By: Relevance
“…Consistently, Tap42 phosphorylation, which mediates its interaction with PP2As, depends on the phosphatidylinositol-related kinases Tor1 and Tor2 ( T arget o f r apamycin), which regulate cell growth in response to nutrient availability and cell stress [58]. The last PP2A subunit that we found in Igo1 immunoprecipitates is Rts3, a poorly characterized protein that was found to interact with different PP2A and PP2A-like complexes [45], [59], [60] and whose deletion causes sensitivity to caffeine [61], which in turn inhibits the Tor complex TORC1 [62].…”
Section: Discussionsupporting
confidence: 57%
“…Consistently, Tap42 phosphorylation, which mediates its interaction with PP2As, depends on the phosphatidylinositol-related kinases Tor1 and Tor2 ( T arget o f r apamycin), which regulate cell growth in response to nutrient availability and cell stress [58]. The last PP2A subunit that we found in Igo1 immunoprecipitates is Rts3, a poorly characterized protein that was found to interact with different PP2A and PP2A-like complexes [45], [59], [60] and whose deletion causes sensitivity to caffeine [61], which in turn inhibits the Tor complex TORC1 [62].…”
Section: Discussionsupporting
confidence: 57%
“…The transient relocalization and the abundance change suggest that Rts3 may play a key role in response to TORC1 inhibition. Indeed, we and others have found that Rts3 is required for cell survival in rapamycin ( Figure 5B) (Parsons et al, 2004;Xie et al, 2005;Hood-DeGrenier, 2011). Thus, flux network-based analysis of the proteome over time can highlight unusual proteome dynamics in response to environmental or genetic stress and facilitate attribution of protein function.…”
Section: Proteins Change In Localization or Abundance But Usually Notmentioning
confidence: 94%
“…5A). Loss of SIT4 and RRD1 have been previously shown to increase caffeine tolerance in high-throughput screens (Kapitzky et al 2010;Hood-DeGrenier 2011), but TIP41 has not. To confirm the contribution of TIP41 S162X we constructed the mutation using CRISPR-Cas9, and observed that TIP41 S162X increased growth in caffeine and rapamycin (Fig.…”
Section: Many Loss-of-function Mutations Contribute To Caffeine and R...mentioning
confidence: 99%